Effects of exposure to mother's and father's alcohol use on young children's normative perceptions of alcohol. (16th September 2022) - Cook, Megan; Smit, Koen; Voogt, Carmen; Kuntsche, Sandra; Kuntsche, Emmanuel
Abstract: Background: While consumption of alcohol does not often begin until early adolescence, young children are highly capable of internalizing normative information through observational learning. We used a longitudinal multiple‐informant family study to examine the impact of exposure to mothers' and fathers' drinking on young children's normative perceptions of who drinks alcohol. Methods: Three hundred twenty‐nine children (4 to 6 years old at baseline [ M age 4.78 (SD = 0.725)], 51% girls) completed the Dutch electronic appropriate beverage task [eABT] where they attributed alcoholic beverages to a variety of persons depicted in an illustrated scenario. Their parents completed an online survey that included information on alcohol use and exposure. Results: Children more frequently exposed to their mothers' drinking provided females shown in the eABT illustrations with alcohol significantly more often than children less frequently exposed to mothers' drinking. There was no effect of mother's exposure on providing males in the eABT with alcoholic beverages. Similarly, children more frequently exposed to their fathers' drinking provided fathers with alcoholic beverages significantly more often than children less frequently exposed to their fathers' drinking. There was no effect of father's exposure on providing the females with alcoholic beverages,  nor was there an effect of father's exposure on providing "other males" with alcohol. These patterns held after adjusting for age and sex. Conclusions: This study demonstrates that there are gender‐specific effects of exposure to parents' (particularly mothers') drinking on young children's perceptions of person‐specific drinking norms. The findings provide unique evidence in a young population group of effects on an understudied dimension of alcohol‐related perceptions with implications for future drinking behavior. Abstract : 329 children (four‐to‐eight years old) completed the Dutch electronic Appropriate Beverage Task [eABT], while parents completed a survey. Children more frequently exposed to their mothers' drinking provided females in the eABT significantly more often with alcohol (β = 1.302, SE = .92***), while children more frequently exposed to their fathers' drinking provided males in the eABT significantly more often with alcohol (β = .663, SE = .249**) than children less frequently exposed to mothers' and fathers drinking respectively. Results demonstrate the gender‐specific effect of exposure to parents drinking.